Effects of aspirin, clopidogrel and dipyridamole administered singly and in combination on platelet and leucocyte function in normal volunteers and patients with prior ischaemic stroke - Zhao, Lian; Fletcher, Sally; Weaver, Chris; Leonardi-Bee, Jo; May, Jane; Fox, Sue; Willmot, Mark; Heptinstall, Stan; Bath, Philip (Thrombosis and Haemostasis, 2005)
The aim of this study was to assess whether triple antiplatelet therapy is superior to dual and mono therapy in attenuating platelet and leucocyte function. Aspirin (A), clopidogrel (C), and dipyridamole (D) were administered singly and in various combinations (A, C, D, AC, AD, CD, ACD), each for two weeks (without washout) to 11 healthy subjects and to 11 patients with previous ischaemic stroke in two randomised multiway crossover trials. At the end of each two-week period platelet aggregation, platelet-leucocyte conjugate formation and leucocyte activation were measured ex vivo blinded to treatment. Platelets were stimulated with collagen; additional measurements were made with adenosine diphosphate (ADP), platelet activating factor (PAF), adrenaline and the combination of, ADP, PAF and adrenaline. Results show that in the presence of collagen, ACD was superior to all antagonists or combinations, except AC, in reducing aggregation, platelet-leucocyte conjugate formation, and monocyte activation (all p< 0.05). ACD was also more potent than other treatments, except AC, in inhibiting the aggregation and platelet-monocyte conjugate formation induced by the combination of ADP, PAF and adrenaline. The effects were similar in both volunteers and stroke patients. No serious adverse events or major bleeding events occurred. Triple antiplatelet therapy did not appear to be more effective than combined aspirin and clopidogrel in moderating platelet and leucocyte function. Any additional clinical benefit provided by dipyridamole may be through other mechanisms of action.
Keywords: Aspirin; clopidogrel; dipyridamole; platelets; ischaemic stroke